Either fadD1 or fadD2, Which Encode acyl-CoA Synthetase, Is Essential for the Survival of Haemophilus parasuis SC096 - Feng, Saixiang; Xu, Chenggang; Yang, Kaijie; Wang, Haihong; Fan, Huiying; Liao, Ming (Frontiers in Cellular and Infection Microbiology, 2017)
In Haemophilus parasuis, the genes HAPS_0217 and HAPS_1695 are predicted to encode long-chain fatty acid CoA ligases (FACSs). These genes contain an ATP/AMP signature and FACS conserved motifs that are homologous to those in Escherichia coli FadD (EcFadD). In this study, we demonstrate that HAPS_0217 and HAPS_1695 can functionally replace EcFadD in the E. coli fadD mutant JW1794, resulting in fadD1 and fadD2, respectively. An evaluation of kinetic parameters indicated that FadD1 and FadD2 have a substrate preference for long-chain fatty acids. Moreover, FadD2 exhibited substrate inhibition in the presence of high concentrations of oleic acid. Single mutants of each of the fadD genes were easily constructed, whereas double mutants were not. These results were further confirmed using genomic site-directed mutagenesis, which supported the notion that both FACSs are essential for H. parasuis survival. The fadD1 mutant exhibited slower growth than the wild-type strain SC096, and its complement showed a restored phenotype. The wild-type strain did not grow on chemically defined medium without the addition of oleic acid, indicating that lipids are a vital nutrient for this bacterium. Additionally, strains with a disrupted fadD1 also exhibited increased sensitivity to quinolone antibiotics, including levofloxacin, enrofloxacin, ciprofloxacin and nalidixic acid.